KEPUASAN BERWIRUSAHA MELALUI KEMAUAN UNTUK BERKARYA USAHA INDUSTRI KECIL - FATKHURAHMAN FATKHURAHMAN (JEBI (Jurnal Ekonomi dan Bisnis Islam), 2016)
The theme of the article is a business based on the principles of Islamic economics. Work becomes a creative product is generated every human being, working also be able to provide additional value to each of the individual votes in the attempt. A strong will to try the human capital and the capital base for every human being to produce a satisfaction in life. Entrepreneurship into land since the former is still an option for every man, but the success of every member in achieving the satisfaction of entrepreneurship is still not optimal and still is questioned by many people. This study attempted to examine whether a strong willingness to work, especially in the small industrial city of Pekanbaru that affect entrepreneurship satisfaction. Small industries and sampled as much as 94 questionnaires were distributed randomly. The research proves that a strong willingness to work positively influence (0.458) and significant (0.000), indicating that the stronger the willingness of managers of small industries to work, the higher the satisfaction gained in entrepreneurship.